The effects of stressful broodstock handling on hormonal profiles and reproductive performance of rhamdia quelen (Quoy & Gaimard) females - Soso, Auren Benk; Gil Barcellos, Leonardo José; Ranzani-paiva, Maria José [UNESP]; Kreutz, Luiz Carlos; Quevedo, Rosmari Mezzalira; Lima, Marina; Bolognesi da Silva, Leonardo; Ritter, Filipe; Bedin, Alexandra Calliari; Finco, Jovani Antônio (My University, 2008)
A stressful environment induces cortisol that might affect fish breeding and reproduction. In the present work, which aimed to mimic aquacultural conditions of the jundia (Rhamdia quelen) hatcheries in southern South America, females were submitted to normal or stressful handling and the effects of cortisol on serum levels of 17β-estradiol (E2) and testosterone (T) were determined. In addition, the effect of stress on reproductive parameters such as eggs and swim-up fry production was also measured. Eight females from a group submitted to stressful handling (SH) conditions and eight females from a group with normal handling (NH) conditions were captured for blood sampling at D 0 and at D 1, 10, 20, 30, and 40 of the experiment. A typical cortisol response was observed in the SH females group in that they presented higher cortisol level in contrast to the NH female group, in all days sampled, except at D 0. In the 10th and 20th d, the E2 levels were lower in SH females, but cortisol levels were higher, suggesting an effect of cortisol on E2 production and/or release. Stressful handling appeared to affect both the number and the quality of the gametes because a lower number of oocytes was stripped from SH females, and from SH fertilized eggs, a lower number of viable swim-up fry was obtained to be transferred to earthen larviculture ponds. Taken together, the results indicated that stressful handling of broodstock impairs R. quelen reproduction. © Copyright by the World Aquaculture Society 2008.
Keywords: aquaculture production; gamete; hatchery; reproductive productivity; South America; Rhamdia quelen